2014
DOI: 10.1093/neuonc/nou020
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic screening identifies a YAP-driven signaling network linked to tumor cell proliferation in human schwannomas

Abstract: Tumor cell proliferation in human schwannomas is linked to a signaling network controlled by the Hippo effector YAP. Her2, Her3, PDGFRß, Axl, and Tie2, as well as YAP, represent potentially valuable therapeutic targets. However, the variability of their expression between tumors may result in strong differences in the response to targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Axl expression has been shown to be important in a wide range of other tumors, [49][50][51][52] including merlin-deficient tumors such as schwannomas and mesotheliomas, 49,53,54 but there are no data available for its potential role in meningiomas. The frequent expression of Axl found in meningiomas in our study suggests that further study of its potential role in meningioma growth is warranted, and if a functional role is confirmed then it offers further therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…Axl expression has been shown to be important in a wide range of other tumors, [49][50][51][52] including merlin-deficient tumors such as schwannomas and mesotheliomas, 49,53,54 but there are no data available for its potential role in meningiomas. The frequent expression of Axl found in meningiomas in our study suggests that further study of its potential role in meningioma growth is warranted, and if a functional role is confirmed then it offers further therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…24 YAP is considered as the main effector of the Hippo signalling pathway in various organisms and tissues. 25 Knockdown of lncRNA GHET1 suppresses the cell proliferation and invasion by down-regulating YAP1 expression in the non-small cell lung cancer. 26 YAP-1 functions as an oncogenic and a putative prognostic biomarker of recurrence in patients with PTC.…”
Section: Discussionmentioning
confidence: 99%
“…29 Dephosphorylated YAP allows its entry into nucleus where it activates the transcription of proproliferative and anti-apoptotic targets. 25 YAP can be phosphorylated and made inactive by alive LATS1. 30 A study has showed that downregulated lncRNA taurine-up-regulated gene 1 (TUG1) occurs with decreased YAP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Merlin is a major regulator of the Hippo signaling pathway by inhibiting the nuclear accumulation of the cotranscription factor Yap and Taz in various organisms (11,12). Although these mechanisms initially appeared distinct, cross talks were identified between several of them (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%